2000
DOI: 10.1016/s0893-133x(99)00149-9
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Opioid Activity Is Associated with Obsessive-Compulsive Symptomology in Individuals with a Family History of Alcoholism

Abstract: Endogenous opioid activity has been associated with the regulation of mood and inhibition of the hypothalamicpituitary-adrenal (HPA) axis. We assessed differences in psychological symptomology and naloxone sensitivity in non-alcoholic males and females with a family history of alcoholism (FHP) and without a family history of alcoholism (FHN).Family history of alcohol dependence is a strong predictor of risk for the future development of alcoholism (Goodwin 1985;Cloninger 1981;McGue et al. 1992). Adult sons of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 91 publications
1
11
0
2
Order By: Relevance
“…Finally, although our sample was small, we demonstrated these findings in a more racially diverse (60% non-Caucasian in the present study vs. 15% in other studies) and older (mean age 33 yrs vs. 21 yrs) group of participants than in many previous studies (Wand et al 1998(Wand et al , 1999aMangold et al 2000), thereby increasing the generalizability of these neuroendocrine effects to more representative samples. In addition to HPA axis differences, we also showed enhanced FHϩ sensitivity to naltrexone in terms of greater mood response, i.e., significant decreases in vigor ratings, which were not present in the FHϪ group.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Finally, although our sample was small, we demonstrated these findings in a more racially diverse (60% non-Caucasian in the present study vs. 15% in other studies) and older (mean age 33 yrs vs. 21 yrs) group of participants than in many previous studies (Wand et al 1998(Wand et al , 1999aMangold et al 2000), thereby increasing the generalizability of these neuroendocrine effects to more representative samples. In addition to HPA axis differences, we also showed enhanced FHϩ sensitivity to naltrexone in terms of greater mood response, i.e., significant decreases in vigor ratings, which were not present in the FHϪ group.…”
Section: Discussionsupporting
confidence: 63%
“…Also, several recent studies have demonstrated that opioidergic hypothalamic sensitivity is greater in high-risk, FHϩ persons (Wand et al 1998(Wand et al , 2001) and may vary as a function of gender (Wand et al 1999a) and degree of obsessive-compulsive symptomatology (Mangold et al 2000). Circadian rhythmicity of cortisol has been found to be similar in FHϩ and FHϪ groups, as well as responses to direct adrenal gland provocation (Wand et al 1999b).…”
Section: Discussionmentioning
confidence: 98%
“…More specifically, tics are presumably due to failed inhibition within cortico-striato-thalamo-cortical circuits. Dysregulation of this circuitry, which is also involved in opiate reward (Mangold et al 2000), may cause a relative lack of serotonin in the feedback loop between the thalamus and the orbito-frontal cortex, the caudate nucleus, and globus pallidus and produce a compensatory increase in 5-HT2A receptor. This mechanism probably underlies the increase in 5-HT2A receptor binding that has been found in the caudate nuclei of untreated patients with OCD (Adams et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…3,14 Son yıl lar da ya pı lan pla se bo kon trol lü bir ça lış ma da; en az iki SGİ' ne ce vap verme yen OKB has ta la rın da te da vi yi güç len dir me de tek doz oral mor fin ve ril di ğin de pla se bo ya gö re anlam lı dü zel me ler ol du ğu be lir til miş tir. 10 APA 2007 OKB te da vi al go rit ma sın da ce vap ver me yen va kalar da de ne ne bi le cek al ter na tif te da vi ola rak öne rilmiş tir. 5 Ol gu muz da ise, ero i ni bı rak tık tan son ra OKB be lir ti le rin de şid det len me görülürken, ero i ne tekrar baş la dı ğın da OKB be lir ti le ri nin kay bol ma sı, yuka rı da ki ça lış ma la rı des tek ler ni te lik te dir.…”
Section: Tar Tiş Maunclassified
“…9 So nuç ola rak; korti ko-lim bik-ba zal gang li yon yo la ğı nın hem OKB hem de opi o id ödül mer ke zi nin kul lan dı ğı or tak yolak olup bu gö rün güy le iliş ki len di ril miş tir. 10 Bi zim va ka mız, psi ko far ma ko lo jik te da vi ye cevap ver me yen OKB has ta sı nın so kak ero i ni kul lanı mı son ra sı re mis yo na gir me si açı sın dan fark lı lık gös te ren bir ol gu dur. Ay rı ca ol gu nun kan şeke ri ni dü şür mek ama cıy la fark lı bir dü şün ce ile ero i ne baş la mış ol ma sı da il gi çe ki ci dir.…”
unclassified